Investigation of bio-kinematic elements of three point shoot in basketball - Hussain, I.; Ahmad, F.; Rani, N. (International Journal of Sports Science, 2017)
This paper mainly used the two dimensional videograph analysis technique to analyze the Three Point Shoot performance of Basketball and to acquire relevant bio-kinematics parameters of the execution of the motion at three different positions ie: right side guard position, left side guard position and centre position. Mainly including the loss rate of body horizontal and vertical velocity of the ball, Wrist angle, Elbow angle, Shoulder angle, Hip angle, Knee angle, Ankle angle, Release height, Release angle and Release velocity, in order to analyze the recording in a more convenient way, we divide Three Point Shooting exertion movement in three phases as Preparation and Ball Elevation phase, Stability and Ball Release phase and Inertia and Follow through phase. Six highly skilled active, north zone intervarsity level, right handed shooters male basketball players were participated in this study. During the Three Point Shooting stages, the initial release shooting velocity of the basketball is 6.89 m/s. The average angle of throwing ball is about 46.61°, with the mean of posture angle remain as 184.52°. And the releasing height of the ball is 2.33 m. This investigation provides kinematics indicators and technical guidance for the training of Three Point Shoot for basketball players.